Genomic surveillance of carbapenem-resistant Acinetobacter baumannii from bloodstream infections in Thailand reveals widespread dissemination of blaNDM–harboring mobile genetic elements - Aekkawat Unahalekhaka; Kulsumpun Krobanan; Watcharaporn Kamjumphol; Phimrata Leethongdee; Yanisa Sukheephak; Patchaya Boonjan; Kasidet Thapaan; Wiphat Klayut; Orapan Sripichai; Nalumon Thadtapong; Chattip Kurehong; Kranokpron Moolwang; et al. (PLoS ONE, 2026)
Carbapenem-resistant Acinetobacter baumannii (CRAB) is a major cause of hospital-acquired bloodstream infections in Thailand, with limited treatment options and a strong association with high morbidity and mortality. We performed nationwide genomic surveillance of 41 CRAB isolates from bloodstream infections collected across Thailand between 2020 and 2024 to characterize the population structure, antimicrobial resistance determinants, and the genomic context of bla NDM -harboring mobile genetic elements (MGEs). Whole-genome sequencing and core genome SNP-based phylogenetic analysis of the Thai samples revealed the dominance of international clone II (Pasteur ST2), which was widely distributed across geographic regions. Carbapenem resistance was primarily mediated by bla OXA-23 , together with intrinsic bla OXA-66 and resistance-associated mutations in a penicillin-binding protein gene. In addition to OXA-type carbapenemase genes, bla NDM-5 and bla NDM-1 were detected in a subset of isolates. In particular, bla NDM-5 was located within a highly conserved MGE associated with a class 1 integron, IS91 family transposase and IS Aba125 and was detected across multiple ST2 sublineages. This MGE was distributed across multiple geographic regions and phylogenetic lineages in Thailand, with evidence suggesting widespread horizontal dissemination followed by local clonal expansion. By contrast, bla NDM-1 was detected less frequently but was consistently associated with a canonical Tn 125 transposon in both ST2 and ST16 isolates, highlighting its continued epidemiological relevance. Collectively, our findings demonstrate that CRAB bloodstream infections in Thailand are driven by a combination of endemic high-risk lineages and the sustained circulation of bla NDM -harboring MGEs. Overall, our results confirm the importance of continued genomic surveillance for monitoring the emergence and dissemination of bla NDM -producing CRAB and for strengthening infection prevention and antimicrobial resistance control efforts in hospital settings.